Supply chain management, inventory management & financial performance: evidence from manufacturing firms - Anantadjaya, Samuel PD; Nawangwulan, Irma M; Irhamsyah, Mohammad; Carmelita, Paula Wendy (Linguistics and Culture Review, 2021)
Supply chain management has always been fascinating to study. Not only goods but also the integration of logistical complexities to meet the requirements of customers or corporations (Extron, 2012). At the same time, inventory management is also fundamental in supply chain management (Dorfman, 1954; Hult et al., 2004). Warehouse management systems play an important role in logistics to maintain effectiveness, controlling movement and storage of materials. This system is critical because it involves chain management. This study strives to find evidence on order picking systems to maximize warehouse space and warehouse performance. Also, this study attempts to test the likelihood that inventory management has a significant influence on financial performance in the manufacturing industry. The methodology relies on qualitative and quantitative approaches to note the successful implementation of the order picking system, and the financial impact. This study provides evidence on the substantial relationships among SCM, inventory management & financial performance.